1980
DOI: 10.3758/bf03197609
|View full text |Cite
|
Sign up to set email alerts
|

Rapid processing of the meaning of sentences

Abstract: It has been shown (Fischler & Bloom, 1979) that sentence contexts facilitate a lexical decision task for words that are highly likely sentence completions and inhibit the decision for words that are semantically anomalous sentence completions. In the present experiment, the sentence contexts were presented 1 word at a time, at rates from 4 to 28 words/sec. The facilitation for words that were likely sentence completions was marginal at the slower rates and absent at higher rates. In contrast, the inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 20 publications
7
58
0
Order By: Relevance
“…Curran and collaborators (1993) observed an ERP component at 136-184 msec that was different for congruent and incongruent sentence endings; the authors noted that the same component was selectively left-lateralized if semantic processing was required. Reading is comfortable at a speed of about five words per second (Fischler & Bloom, 1980) and semantic priming effects occur if only 250 msec are available to process the prime (Neely, 1977). In agreement with the present results, these observations suggest that at least some of the semantic processing of incoming information occurs within the first 200 msec.…”
Section: Discussionsupporting
confidence: 90%
“…Curran and collaborators (1993) observed an ERP component at 136-184 msec that was different for congruent and incongruent sentence endings; the authors noted that the same component was selectively left-lateralized if semantic processing was required. Reading is comfortable at a speed of about five words per second (Fischler & Bloom, 1980) and semantic priming effects occur if only 250 msec are available to process the prime (Neely, 1977). In agreement with the present results, these observations suggest that at least some of the semantic processing of incoming information occurs within the first 200 msec.…”
Section: Discussionsupporting
confidence: 90%
“…From the monolingual domain it is well known that the semantic and syntactic framework that one constructs when reading a sentence provides an important topBilingual Word Recognition in Sentences 4 down influence on lexical access of the words appearing further in the sentence. For example, there is ample evidence that more predictable words are processed faster in a variety of production and recognition tasks such as naming (e.g., McClelland & O'Regan, 1981;Stanovich & West, 1983), lexical decision (e.g., Fischler & Bloom, 1979;Fischler & Bloom, 1980;Schwanenflugel & Lacount, 1988;Schwanenflugel & Shoben, 1985) and speech monitoring (e.g., Cole & Perfetti, 1980). Similarly, eyetracking studies have consistently shown that more predictable words are skipped more often, and yield shorter fixation times (e.g., Balota, Pollatsek, & Rayner, 1985;Ehrlich & Rayner, 1981;Rayner & Well, 1996).…”
mentioning
confidence: 99%
“…This evidence connects to discussions in the RT priming literature, where it has been something of an issue whether an essentially meaningless real word (such as blank) is to be preferred over a string of nonletter symbols (e.g., asterisks, hash marks) as the neutral prime stimulus and, more in general, whether a truly neutral stimulus can be achieved at all (cf. De Groot, Thomassen, & Hudson, 1982;Fischler & Bloom, 1980;Shelton & Martin, 1992). This issue is examined under General Discussion, following which the remainder of the discussion focuses on the implications of the results obtained for the target words.…”
mentioning
confidence: 99%